2008
DOI: 10.1021/ol802339w
|View full text |Cite
|
Sign up to set email alerts
|

Englerin A, a Selective Inhibitor of Renal Cancer Cell Growth, from Phyllanthus engleri

Abstract: An extract from Phyllanthus engleri was identified in a bioinformatic analysis of NCI 60-cell natural product extract screening data, that selectively inhibited the growth of renal cancer cell lines. Bioassay guided fractionation yielded two new guaiane sesquiterpenes, englerins A (1) and B (2). Englerin A showed 1000-fold selectivity against 6 of 8 renal cancer cell lines with GI50 values ranging from 1-87 nM. The structures of 1 and 2 and their relative stereochemistry were established by spectroscopic metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
183
0
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(202 citation statements)
references
References 17 publications
6
183
0
10
Order By: Relevance
“…The spectroscopic data of our synthetic 1 are in agreement with those reported for natural englerin A. [1,19] In conclusion, an asymmetric total synthesis of (À)-englerin A has been achieved in 15 steps with 8.1 % overall yield by starting from (R)-citronellal. The synthesis is concise and features several key transformations, namely, a goldcatalyzed cyclization of an enyne and a hydroxy-directed hydrogenation of an olefin.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…The spectroscopic data of our synthetic 1 are in agreement with those reported for natural englerin A. [1,19] In conclusion, an asymmetric total synthesis of (À)-englerin A has been achieved in 15 steps with 8.1 % overall yield by starting from (R)-citronellal. The synthesis is concise and features several key transformations, namely, a goldcatalyzed cyclization of an enyne and a hydroxy-directed hydrogenation of an olefin.…”
supporting
confidence: 83%
“…[1] This species was collected from a plant growing in East Africa. Biological evaluation revealed that englerin A has potent ability to inhibit renal cancer cell growth with GI 50 values (growth inhibition of 50%) ranging from 1-87 nm.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Further column chromatography (CC) over Diaion HP20SS, Sephadex LH-20 and silica gel, followed with semipreparative HPLC purification of the MeOH extract yielded five new compounds (1)(2)(3)(4)(5), together with two known ones. The known compounds were elucidated as jasminoside (6) 6 and jaslanceoside B (7) 7 by comparison of their spectroscopic data with reported literature values.…”
Section: Resultsmentioning
confidence: 99%
“…Previous chemical studies on this genus have revealed the occurrence of flavonoids, alkaloids, sesquiterpenoids, triterpenoids, lignans, and tannins. [1][2][3][4][5] Among them, some sesquiterpenoids exhibited potent antiviral activity against coxsackie virus B3 (CVB3), 4 and inhibition of the growth of murine P-388 lymphocytic leukemia cell line. 5 P. cochinchinensis, a shrub up to 3 m height, is mainly growing in the montane sparse forests, forest margins, scrub on slopes, and wastelands of the southern part of China.…”
Section: Introductionmentioning
confidence: 99%